2017
DOI: 10.4103/1008-682x.173936
|View full text |Cite
|
Sign up to set email alerts
|

Oviductal epithelial cells selected boar sperm according to their functional characteristics

Abstract: The interaction of oviductal epithelial cells (OECs) with the spermatozoa has beneficial effects on the sperm functions. The aim of this study is to evaluate the in vitro fertilizing capacity of incubating spermatozoa previously selected by density gradient in OEC and determinate some sperm characteristics that could explain the results obtained. In this study, we assessed in vitro fertilization (IVF), tyrosine phosphorylation, phosphatidylserine translocation, nuclear DNA fragmentation, and chromatin deconden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…The binding of spermatozoa to oviductal cells forms a reservoir 43 which is mediated by carbohydrates on the oviductal cell apical membranes and lectin-like molecules on the sperm surface 44,45 . Several studies have shown that oviductal epithelial cells select boar spermatozoa according to their functional membrane-mediated characteristics 36,46,47 . The slightly reduced binding capacity of spermatozoa stored at 5° observed in the present study may be attributed to chilling-induced membrane lipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of spermatozoa to oviductal cells forms a reservoir 43 which is mediated by carbohydrates on the oviductal cell apical membranes and lectin-like molecules on the sperm surface 44,45 . Several studies have shown that oviductal epithelial cells select boar spermatozoa according to their functional membrane-mediated characteristics 36,46,47 . The slightly reduced binding capacity of spermatozoa stored at 5° observed in the present study may be attributed to chilling-induced membrane lipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as we know, sperm membrane is the interaction site of male gametes with the surrounding environment and, consequently, it is involved in the information exchange that leads the spermatozoa to the acquisition of full fertilizing ability. Several reports agree in describing two different pools of male gametes within the oviduct: one group of spermatozoa present within the lumen, not bound to the epithelial cells and characterized by poor viability and unable to fertilize, and another group, encompassing spermatozoa attached to the OECs with potentially capacitated cells that will be able to fertilize the oocyte 58 . To date, the specific molecular mechanisms involved in such interaction are not completely understood, but it has been supposed that the membrane glycocalyx could be involved 40 .…”
Section: Discussionmentioning
confidence: 97%
“…A plethora of in vitro studies supports this narrative (see Table 2). Overall, they show that OECs preferentially bind uncapacitated sperm [64,93,100,101] with higher DNA integrity [102,103]. Some of the differences observed between bound and free-swimming sperm were detected only after 3 minute of incubation [93].…”
Section: Boar Ex Vivo Oviduct Explantmentioning
confidence: 87%
“…There are several studies showing that sperm incubation with OECs can improve IVF success, perhaps due to effects on sperm adhesion to the OECs [64][65][66]. Sperm heads bind specific oligosaccharides containing glycan motifs that are part of the OECs glycocalyx (see reviews [67,68]).…”
Section: Sperm Storage In the Isthmusmentioning
confidence: 99%